Brainstem Cavernous Malformations Management: Microsurgery vs. Radiosurgery, a Meta-Analysis - Fotakopoulos, George; Andrade-Barazarte, Hugo; Kivelev, Juri; Tjahjadi, Mardjono; Goehre, Felix; Hernesniemi, Juha (Frontiers in Surgery, 2022)
Given the rareness of available data, we performed a systematic review and meta-analysis on therapeutic strategy microsurgical resection and stereotactic radiosurgery (SRS) for brainstem cavernous malformations (BSCMs) and assessed mortality, permanent neurological deficits (PNDs), rebleeding rate, and patients who require reintervention to elucidate the benefits of each treatment modality. Preferred reporting items for systematic reviews and meta-analyses (PRISMA) were used for protocol development and manuscript preparation. After applying all inclusion and exclusion criteria, six remaining articles were included in the final manuscript pool. In total, this meta-analysis included 396 patients, among them 168 patients underwent microsurgical treatment and 228 underwent SRS. Findings of the present meta-analysis suggest that regarding the total group of patients, in terms of mortality, late rebleeding rate, and PNDs, there was no superiority of the one method over the other. Applying the leave-one-out method to our study suggests that with low robust of the results for the bleeding rate and patients who require reintervention outcome factor, there was no statistical difference among the surgical and SRS treatment. Microsurgical treatment of BSCMs immediately eliminates the risk of rehemorrhage; however, it requires complete excision of the lesion and it is associated with a similar rate of PNDs compared with SRS management. Apparently, SRS of BSCMs causes a marked reduction in the risk of rebleeding 2 years after treatment, but when compared with the surgical treatment, there was not any remarkable difference.